Oral Exposure to Titanium dioxide nanoparticles: a Systematic Literature Review as a tool to develop Adverse Outcome Pathway landscapes and supporting in vitro assays - Rolo, Dora (2022)
Despite being considered key enabling technologies, the exponential use of nanoparticles in food technology leads to concerns about adverse health outcomes upon ingestion. The use of Titanium dioxide nanoparticles (TiO2-NPs) as a food additive was considered no longer safe by the European Food Safety Authority (EFSA) in 2022, and the European Commission announced the decision to ban its use. Nevertheless, other products containing TiO2-NPs, such as pharmaceuticals, personal hygiene, or cosmetics, that are not covered in the food regulation, may lead to ingestion of TiO2-NPs. In this regard, further research is needed. A valuable tool is the establishment of Adverse Outcome Pathways (AOPs) landscapes, which contributes to support risk assessment and may drive policy decisions. AOPs describes a sequence of causally linked events at different levels of biological organization leading to adverse health effects. Our main goal was to further understand the molecular and cellular mechanisms, triggered after the ingestion of TiO2-NPs. A systematic literature review was performed, integrating information produced on this topic and provide data for a standardized assessment of the evidence. AOP landscapes were proposed in order to identify mechanisms that mediate adverse outcomes, and additional in vitro assays were performed. Our in vitro findings suggest that part of the ingested TiO2-NPs can be transcytosed through colonic epithelia without disrupting intestinal barrier integrity. These results are consistent with our AOPs proposal where colorectal cancer, liver injury, reproductive toxicity, cardiac and kidney damage, as well as hematological effects stand out as possible adverse outcomes. Based on a mechanistic reasoning, this study contributes to increase the understanding of ingested TiO2-NPs kinetics, their bioavailabity to induce systemic effects crossing the intestinal barrier and potential fate in Humans. Overall, the findings further support a limitation of the use of TiO2-NPs in food, as announced by EFSA.